The Teaching of Social Studies: An Approach to Alternative Routes of Academic Interpretation - Solano Pérez, Carlos Daniel (2021)
Thinking about the Teaching of Social Studies, from its academic field position, is a debt in the national debates, which reveals a significant limitation to reach discussions of a theoretical and epistemological nature. This article seeks to contribute to the debate of the investigative aspects, through the analysis of a current state of research, based on the Final Graduation Projects. Consequently, the purpose of this research lies in the structuring of an alternative epistemological interpretation route, based on the concept of Didactics of Social Studies.